2007
DOI: 10.1158/0008-5472.can-07-2226
|View full text |Cite
|
Sign up to set email alerts
|

Gpx2 Is an Overexpressed Gene in Rat Breast Cancers Induced by Three Different Chemical Carcinogens

Abstract: Gene expression alterations are essential for the process of carcinogenesis. A carcinogen may have specific mechanisms for inducing tumors, which may involve inducing characteristic gene expression alterations. In this study, we attempted to identify genes crucial for mammary carcinogenesis. For this purpose, we used human c-Ha-ras proto-oncogene transgenic rats (Hras128), which are highly sensitive to mammary carcinogens including N-methyl-N-nitrosourea, 7,12-dimethyl benz[a ]anthracene, and 2-amino-1-methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…In addition, mice lacking the GPx2 gene are characterized by an increased sensitivity to UV-induced skin cancer development (363), whereas the double GPx1/GPx2 knockout mice demonstrated the development of spontaneous colitis and intestinal cancer (64). However, expression of GPx2 has also been shown to be regulated by the Wnt pathway, which is involved in activation of cellular proliferation, and knockdown of GPx2 in rat and human cancer cells resulted in significant growth inhibition (263) and induction of apoptosis (375). Together, these observations indicate that GPx2 might have a dual role in cancer similar to thioredoxin reductase 1 and Sep15 (discussed below) by both preventing and promoting tumor cell growth at the later stages of cancer development.…”
Section: Selenoprotein Functionmentioning
confidence: 99%
“…In addition, mice lacking the GPx2 gene are characterized by an increased sensitivity to UV-induced skin cancer development (363), whereas the double GPx1/GPx2 knockout mice demonstrated the development of spontaneous colitis and intestinal cancer (64). However, expression of GPx2 has also been shown to be regulated by the Wnt pathway, which is involved in activation of cellular proliferation, and knockdown of GPx2 in rat and human cancer cells resulted in significant growth inhibition (263) and induction of apoptosis (375). Together, these observations indicate that GPx2 might have a dual role in cancer similar to thioredoxin reductase 1 and Sep15 (discussed below) by both preventing and promoting tumor cell growth at the later stages of cancer development.…”
Section: Selenoprotein Functionmentioning
confidence: 99%
“…DNA microarray analysis shows that glutathione peroxidase (Gpx) 2 was commonly up-regulated in mammary carcinomas induced by the three carcinogens, MNU, DMBA and 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) due to activation of ER-a via the Raf/Ras/MAPK cascade. In addition, it has been reported that the forced suppression of Gpx2 expression by siRNA resulted in significant growth inhibition in rat and human mammary carcinoma cell lines with wild type p53 cells indicating that Gpx2 may be a novel target for the prevention and therapy of breast cancer [169].…”
Section: Modulation Of Intermediate and Endpoint Biomarkers By Terpenmentioning
confidence: 99%
“…The H 2 O 2 produced by SOD activity is metabolized by the two downstream enzymes; catalase and GPx. Though liver is known to express many GPx isoforms, mainly GPx1 and GPx2 have been found associated with the tumor development [16,17].…”
Section: Introductionmentioning
confidence: 99%